ASEAN university network quality - assurance guidelines - ASEAN University Network ([Indonesia ASEAN University Network, 2004)
This AUN-QA guidelines was jointly written by the CQOs to be used as a manual and reference for the distinct and unique QA movement in the ASEAN region.
Keywords: ASEAN University Network; Education, Higher -- Standards -- Asia; Universities and colleges -- Standards -- Asia; Quality assurance -- Asia